The Deterrent Effect of Employee Whistleblowing on Firms' Financial Misreporting and Tax Aggressiveness - Wilde, Jaron H. (The Accounting Review, 2017)
ABSTRACT U.S. laws provide explicit whistleblower protections and direct regulators to adopt ambitious programs to reward whistleblowing. However, there is limited evidence on whether employee whistleblowing deters financial misreporting and tax aggressiveness. Using a sample of employee whistleblower cases obtained from the U.S. government, I provide evidence that firms subject to whistleblowing allegations exhibit significant decreases in financial misreporting and tax aggressiveness, compared with control firms. I find that this deterrent effect persists for at least two years beyond the year of the allegation. JEL Classifications: H25; M41; M48. Data Availability: All data are available from public sources identified in the paper.